Rationalising laboratory workflow to improve the efficiency of diagnostic service delivery: A critical review of haematological malignancies by flow cytometric immunophenotyping at the Charlotte Maxeke Johannesburg Academic Hospital - Naidoo, Maynolia (University of the Witwatersrand, Johannesburg, 2023)
The 2006 Bethesda medical indications guideline provides concise indications for flow cytometric immunophenotyping (FCI), to enable rationalising a decision for sample processing. The local practice of processing every sample received for FCI places an enormous burden on the resources of the laboratory, and leads to unnecessary expenditure for state health. A ‘triage’ process based on the current Bethesda medical indications guideline may be beneficial in developing countries. The aim of this study was to determine how the implementation of a triage process would impact on the diagnostic service delivery, and the ability to detect or miss disease. A retrospective review of 500 bone marrow aspirate (BMA) samples submitted for FCI analysis was performed from October to December 2019. The sensitivity, specificity, and predictive values of the BMA cytomorphology against the FCI outcomes (‘test-all’) were determined. Thereafter, the Bethesda medical indications guideline was retrospectively applied to the same data set (‘triage’), to compare the decision to process or not to process samples, against objective evidence of disease in various BMA investigations. After exclusion of inadequate quality samples that preclude comparison, 429 ‘test-all’ and 455 triage cases were evaluated. The ‘test-all’ analysis revealed a 97.1% sensitivity and 89.8% specificity, with a 64.1% positive predictive value (PPV) but striking 99.4% negative predictive value (NPV). The triage was largely effective in identifying cases with disease, revealing a 100% sensitivity and 83.3% specificity, with a PPV of 32.5% and very high NPV of 93.8%. Without impacting clinical outcomes, the implementation of a triage process can reduce the burden of FCI testing by 18%. Preliminary cytomorphological review of the accompanying BMA is strongly recommended as an additional step to improve the overall PPV of the triage, while safely reducing unnecessary FCI sample processing in a further 56% of cases. The implementation of a triage process with modifications for local use in flow cytometry laboratories, would enable the appropriate rationalisation of resources, improve the cost- effectiveness, and overall diagnostic service delivery in developing countries like Sub-Saharan Africa
A research report submitted in fulfillment of the requirements for the degree of Master of Medicine in Haematological Pathology to the Faculty of Health Sciences, University of the Witwatersrand, School of Pathology, Johannesburg, 2023
Keywords: Medical indication; Flow cytometric immunophenotyping (FCI); UCTD; SDG-3: Good health and well-being